Group Psychotherapy Research Studies That Therapists Might Actually Read: My Top 10 List. Issue 1 (2nd January 2017) - Greene, Les R.
ABSTRACT: Much like a bad marriage, the longstanding split between psychotherapy practitioner and researcher continues, each partner feeling unappreciated by and blaming of the other: Therapists are criticized for not reading research and, in turn, criticize researchers for their pursuit of studies that seem irrelevant to the clinical enterprise. In the present article, the author proposes that a shift in the design of psychotherapy research, away from pure outcome studies to models that focus on process, may serve to bridge the divide. Ten research designs exploring aspects of the process of group psychotherapy are illustrated from the recent literature, with the aim of furthering the dialogue between practitioner and researcher.